The Application of Hypnosis in Sports - Li, Zhe; Li, Su-Xia (Frontiers in Psychology, 2022)
As an ancient science, hypnosis has been used by humans since the primitive societies during theocratic times. By the 20th century, scientists and psychologists had re-recognized and studied hypnosis and explored its applications in fields such as medicine, education, and military uses. A local form of traditional Chinese “hypnosis” appeared in Huangdi Neijing, but it has not received enough attention from Chinese people; China’s modern hypnosis development is later than that of American and European countries. Therefore, people’s understanding and applications of hypnosis remain inadequate. With the development of China’s economy and state power in the last decades, Chinese people were beginning to attach importance to the investment and development of the sports industry and realized that the psychological quality of the athletes is often a decisive factor in the success or failure of the competition. Meanwhile, hypnosis is an effective psychological training method to be used in daily training and competitions. In light of this, this essay firstly reviews the history of hypnosis before carrying out the methods of a literature review and a logical analysis to explore the applications of hypnosis in sports. Thus, evidence is provided in favor of the use of hypnosis in the sports industry.